Hemorrhagic Wallenberg Syndrome Accompanied by Horner Syndrome at Young Age - Imran I; Lailatul Fadhila (AKSONA, 2023)
Highlight: Wallenberg syndrome caused by medulla oblongata hemorrhage with good functional outcome. Wallenberg syndrome is accompanied by Horner's syndrome, which occurs at a young age. In patients with Wallenberg syndrom, conservative management and medical rehabilitation are used.   ABSTRACT Introduction: Wallenberg syndrome is a rare syndrome involving the medulla oblongata, an uncommon hemorrhage site. It is also known as lateral medullary syndrome or posterior inferior cerebellar artery syndrome. Wallenberg syndrome has several symptoms that can be divided into vestibulo-cerebellar, bulbar, autonomic, sensory, and atypical. Case: A 27-year-old man came to the emergency unit complaining of dizziness and swinging, as well as a left eyelid that did not open completely, a lack of sweat on the left side of the face, a hoarse voice, swallowing disturbances, hiccups, decreased hearing in the left ear, and a lack of sensation on the left side of the face and the right side of the body. The patient tended to fall to the left and was unsteady when standing. Physical examination revealed Horner syndrome, bidirectional nystagmus, left dysdiadochokinesia, and left ataxia. A CT scan of the head showed a left-sided medulla oblongata hemorrhage. The patient was given conservative therapy, feeding through a nasogastric tube, and medical rehabilitation. A repeat CT scan of the head was done one week later, and it was discovered that the hemorrhage in the medulla oblongata had begun to absorb. Conclusion: Wallenberg syndrome, with a manifestation of hemorrhagic stroke in the medulla oblongata, can occur at a young age with various clinical symptoms. The diagnosis of Wallenberg syndrome is made based on clinical symptoms and imaging findings. Conservative therapy using medicines and medical rehabilitation can provide a speedy recovery. An incorrect diagnosis is a major hazard to patient safety and can have serious consequences, including permanent disability or death.